Factors affecting the behavior of captive white rhinoceros (Ceratotherium simum) and the accuracy of ad‐hoc keeper data. Issue 1 (5th August 2022) - Goodenough, Anne E.; Price, Thomas W.; Brazier, Danica L.; McDonald, Katie
Abstract: Although white rhinoceros ( Ceratotherium simum ) are common in captivity, few behavioral studies have been conducted and there is seemingly no research for immersive exhibits where potential for visitor effects is high. Moreover, little information exists on possible effects of weather and temperature on rhino outside their native range. Here we analyze 14, 501 observations of rhino in a drive‐through enclosure. Data were collected by researchers ( n  = 12, 160 datapoints) and keepers ( n  = 2341 datapoints) over a 4‐month period. We aimed to: (1) quantify behavior using detailed researcher‐collected data and contemporaneous but ad hoc keeper‐collected data; (2) compare datasets statistically; (3) establish effects of visitors, temperature, and weather on behavior; and (4) assess the influence of visitors on similarity of researcher/keeper datasets. Activity budgets were similar to the wild and the single previous study from a traditional (nondrive‐through) enclosure. There was some discrepancy in activity budgets between researcher and keeper data due to significant differences in recorded frequency of two rare behaviors (horn rub; social interaction) and two behaviors that could be easily confused (grazing vs. standing with head‐down): recording of other behaviors matched well. Weather and temperature affected behavior, with rhino becoming more sedentary (−locomotion, grazing; +resting, standing, and sedentary eating of hay) on hot/sunny days compared to cool/wet days. The number of visitor vehicles had a fairly negligible effect but resting was lower on busy days, possibly as vigilance increased. The match between researcher/keeper datasets was lowest when visitor numbers were high, suggesting visitors might affect keeper ability to accurately record behavior. Abstract : Comparison of methods used to quantify rhino behavior and influence of external factors on behavioral profile Research highlights: Rhino were more sedentary (− walking/grazing; + resting/standing) on hot and sunny days. Visitors had a negligible behavioral effect. Keeper versus researcher data matched well overall but differed for specific behaviors and with high visitor numbers.